SEMANTIC STRUCTURE OF WORDS RELATED TO EDUCATION IN ENGLISH AND UZBEK LANGUAGES - Аkhmedov Oybek; Tilavova , Malika (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
The article is devoted to combinatorial semasiology, which is a description of the relationship between word semantics and its coherence. A word has a specific meaning to join with another word in which its cognate is already included, which is an important correct linguistic indicator of this meaning. The semantic structure of words related to education in English and Uzbek languages is discussed and reflected in examples. Also, the study of several methods of semanticizing words is carried out in this article.